2018
DOI: 10.1002/prp2.433
|View full text |Cite
|
Sign up to set email alerts
|

The role of loops B and C in determining the potentiation of GABAA receptors by midazolam

Abstract: Many benzodiazepines are positive allosteric modulators (PAMs) of GABAA receptors that cause sedation, hypnosis, and anxiolysis. Benzodiazepines bind GABAA receptors at the extracellular interface of the α and γ subunits. Within the α subunit, the benzodiazepine binding site is defined by three highly conserved structural loops, loops A‐C. Although previous mutagenesis studies have identified His102 in Loop A as important for benzodiazepine modulation of GABAA receptors, the functional roles of many of the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Given that the high affinity binding site exists at the α–γ interface, a multitude of side effects can occur following administration due to their non-selective targeting of GABA A Rs. Classical benzodiazepines interact non-selectively with all GABA A Rs containing α1-, α2-, α3-, α5-, and γ2 subunits ( Moody and Jenkins, 2018 ). Whereas α1-containing GABA A Rs have the greatest distribution throughout the brain ( Möhler et al, 2002 ), α2-, α3-, and α5-containing GABA A Rs are expressed with greater confinement to specific brain regions ( Engin et al, 2018 ).…”
Section: Benzodiazepine Actions On Gaba a Rsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the high affinity binding site exists at the α–γ interface, a multitude of side effects can occur following administration due to their non-selective targeting of GABA A Rs. Classical benzodiazepines interact non-selectively with all GABA A Rs containing α1-, α2-, α3-, α5-, and γ2 subunits ( Moody and Jenkins, 2018 ). Whereas α1-containing GABA A Rs have the greatest distribution throughout the brain ( Möhler et al, 2002 ), α2-, α3-, and α5-containing GABA A Rs are expressed with greater confinement to specific brain regions ( Engin et al, 2018 ).…”
Section: Benzodiazepine Actions On Gaba a Rsmentioning
confidence: 99%
“…This can prove to be problematic when considering off-target drug effects and unforeseen complications from drug administration due to drug binding across many GABA A R subtypes in different brain regions. Considering the nature of current GABA A R pharmaceuticals, the design of these drugs is based on previously characterized binding sites, such as the high affinity benzodiazepine binding site which exists between the α and γ subunits ( Moody and Jenkins, 2018 ). However, there is still a lack of new and clinically relevant subunit-specific GABA A R-targeting drugs despite scientific success in furthering our understanding of GABA A R structure and function ( Figure 1 ).…”
Section: Summary and Future Outlookmentioning
confidence: 99%
“…Thereafter, multiple variants of the α (1–6), β (1–3) and γ (1–3) subunits were discovered [ 28 ], whose combinations confer differential effects of BZDs [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The cloning of GABA A R subunits enabled the molecular mechanism of BZD modulation to be probed via mutagenesis, which has led to numerous studies that identified not only the binding site but also the regions contributing to the drug’s modulatory effect.…”
Section: A Brief Historymentioning
confidence: 99%
“…Mutagenesis and photoaffinity labeling identified a region in the extracellular domain (ECD) at the α+/γ− subunit interface as the location of the high-affinity BZD binding site where mutations often impaired BZD binding or the modulation of GABA-evoked responses [ 34 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] ( Figure 1 A,B). Cryo-EM structures confirmed this as a recognition site for BZDs [ 42 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Canonical Extracellular High-affinity Binding Sitementioning
confidence: 99%
“…20 Interestingly, even though midazolam potentiates α 5 -containing GABA A receptors in a similar concentration range as α 1 - and α 2 -subunits, it is most efficacious on α 1. 21 This may imply that a complex interplay of all three subunits in the hippocampus is involved in the drug’s amnesic properties. In the current study, we first investigated the contribution of α 1 -, α 2 -, and α 5 -subunits on midazolam’s actions on long-term potentiation evoked in hippocampal brain slices and finally detailed the midazolam effect on synaptic inhibition in wild-type and α 2/3/5 –knock-in mice.…”
mentioning
confidence: 99%